Molecular insights into antimicrobial resistance and virulence in hospital-associated of vancomycin-resistant Enterococcus faecium isolates in a tertiary hospital in Bangkok Thailand - Thanwa Wongsuk; Anchalee Homkaew; Worrapoj Oonanant; Uraporn Phumisantiphong; Daranee Nutalai; Pranchalee Utaranark; Siriphan Boonsilp (PLoS ONE, 2026)
Vancomycin-resistant Enterococci (VRE) are major pathogens causing nosocomial infections globally. This study investigated the genetic characteristics of vancomycin-resistant Enterococcus faecium (VREfm) in Thailand between June and November 2022. Fifty-two clinical VREfm isolates from Bangkok hospitals were analyzed for antimicrobial susceptibility, resistance genes, virulence factors, and genotypes using multilocus sequence typing (MLST). Phylogenetic analysis and goeBURST assessed genetic relationships and population structure. The VRE detection rate was 14.5%, with 97.1% E. faecium and 2.9% E. faecalis , likely reflecting the impact of an active case-finding program. All isolates exhibited resistance to penicillin, ampicillin, vancomycin, levofloxacin, ciprofloxacin, and rifampin. Resistance to erythromycin, high-level streptomycin, teicoplanin, and tetracycline occurred in 98.1%, 53.8%, 51.9%, and 17.3% of isolates, respectively. Chloramphenicol, linezolid, and high-level gentamicin remained effective against all isolates. The van A gene was the sole resistance determinant detected. Virulence genes esp and hyl were present in 100% and 88.5% of isolates, respectively. MLST identified five sequence types (STs), with ST17 (86.5%) as the dominant lineage, followed by ST262 (7.7%), ST202, ST787, and ST80 (1.9% each). All isolates belonged to Clonal Complex 17. Genome analysis revealed various resistance genes (VanHAX, aac (6')-Ii, aad (6), ant(6)-Ia , msr C, and tet M) and virulence factors ( acm , bop D, cps A/ upp S, cps B/ cds A, ebp A, ebp B, ebp C, efa A, esp , sgr A, and srt C). The van A gene primarily drives vancomycin resistance in Thailand’s VREfm. Genome analysis reveals antibiotic resistance genes, virulence factors, and mobile genetic elements that may drive antimicrobial resistance, increase diversity, and support adaptation in hospital settings. Ongoing infection control and active surveillance are essential.